CEREALS PRODUCTION BETWEEN CLIMATE CHANGE AND PRICE BOOM IN ROMANIA - Agatha POPESCU; Cristina TINDECHE; Alina MARCUTA; Liviu MARCUTA; Adelaida HONTUS (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of this research work was to analyze cereals cultivated area, yields, production and price at farm gate in Romania during the last decade, 2012-2021 and also in the year 2022 in order to identify the main trends and causes which affected the performances. The data provided by National Institute of Statistics and Eurostat were processed using indices methods, regression equations and r square, and comparisons between maize and wheat. The results emphasized that, compared to 2012 level, in 2021, Romania achieved 27.79 million tonnes cereals (+116.27%), 14.82 million tonnes maize grains (+149.07%), and 10.43 million tonnes wheat (+96.79%). Maize and wheat represent 92.8% of Romania's cereals production. The high record is explained by the large surfaces cultivated with cereals, accounting for 5.35 million ha in 2021 (-1.6% less than in 2012), of which maize 47.6% and wheat 40.6%, all together 88.2%. Yields are still below the levels achieved by France, Germany, Poland, Italy and Spain, which are its EU main competitors in producing cereals. Compared to 2012, in 2021, cereals yield was 5,188 kg/ha (+120%), maize 5,802 kg grains/ha (+166.16%), wheat 4,797 kg/ha (+78.85%), reflecting the efforts made by farmers to increase production. These results were carried out under the impact of intense climate variations and extreme phenomena like: high air temperatures, heat waves, long droughts, low precipitations. High price volatility for Diesel, seeds, fertilizers, products for plant protection etc had a deep impact on the increase of production costs. Cereals price at the farm gate also increased, under the influence of the unbalance demand/supply ratio in the international market, cereals quotations at the international stock exchange, and hostilities between Russia and Ukraine. Un uncertain future is for the coming agricultural years, when farmers have to strengthen their efforts as their business to survive. They have to set up new technological alternatives for crop structure, cultivated areas, amendments, conservative agriculture, lower farms inputs, environmentally friendly solutions to sustain soil fertility, extend biodiversity, and also to keep production costs under strict control and to assure a lower risk for their business.